2018
DOI: 10.1111/ppe.12481
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced identification of maternal hepatitis C virus infection using existing public health surveillance systems

Abstract: Maternal HCV infection is under-recognized and increasing in prevalence. Current case identification processes are inadequate in pregnancy, even among women with prior positive HCV testing. Alternative approaches, including enhanced risk factor-based screening or universal prenatal screening in high prevalence settings, are needed to improve rates of HCV recognition among reproductive-aged women and newborns at risk of vertical transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…As mentioned above, there is risk for vertical transmission among younger women living with HCV who become pregnant. A number of population-based studies in the US have indicated that rising maternal and pediatric HCV prevalence is likely related to concomitant increasing opioid use among women of reproductive potential [ 3 , 36 38 ]. In the BC Hepatitis Testers Cohort, 61% of women with chronic HCV infection who were born after 1975 had histories of injection drug use and opiate use, among whom 50% had not been treated for HCV as of 2019.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, there is risk for vertical transmission among younger women living with HCV who become pregnant. A number of population-based studies in the US have indicated that rising maternal and pediatric HCV prevalence is likely related to concomitant increasing opioid use among women of reproductive potential [ 3 , 36 38 ]. In the BC Hepatitis Testers Cohort, 61% of women with chronic HCV infection who were born after 1975 had histories of injection drug use and opiate use, among whom 50% had not been treated for HCV as of 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of hepatitis C virus (HCV) infection has increased among pregnant women in recent years (150)(151)(152)(153). HCV screening should be performed for all pregnant women during each pregnancy, except in settings where the HCV infection (HCV positivity) rate is <0.1% (154)(155)(156).…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…HCV testing in BC is estimated to be 3.5-fold higher than in the US, and our finding related to the declining number of positive tests among prenatally screened women in BC suggests that more who are at low-risk are being tested and/or that fewer women who are pregnant or planning pregnancy are at risk of HCV infection. Moreover, several population-based studies in the US have indicated that rising maternal and pediatric HCV prevalence is likely related to concomitant increasing opioid use among women of childbearing age [6,[29][30][31]. Future exploration into differences between women in BC who had a prenatal anti-HCV test vs. those who did not will help better understand the testing trends we have found in this study, especially to evaluate the utility of risk-based testing guidelines when it appears that more healthcare providers are opting to test women with lower risk.…”
Section: Discussionmentioning
confidence: 99%